Hydrothermal crafting of azine-linked covalent organic frameworks: synthesis and characterization - Ling, Jun Ni; Low, Wei Yee; Rubena Yusoff; Moh, Pak Yan; Norini Tahir (Universiti Malaysia Sabah press, 2024)
The objective of this study is to develop a covalent organic framework (COF) with high nitrogen content using a mild and environmentally friendly synthesis methodology. Specifically, we synthesized an azine-linked covalent organic framework (HACOF) utilizing 1,3,5-triformylbenzene and hydrazine as monomers, with water as a green solvent. The structural formation of HACOF was confirmed by FTIR spectroscopy, which indicated the presence of azine linkages. Elemental analysis further supported the successful incorporation of nitrogen within the framework. Crystallographic analysis revealed that HACOF exhibited moderately high diffraction peaks at 2Θ = 25.31° and 26.22°, indicative of a well-ordered structure. Thermogravimetric analysis demonstrated that HACOF is thermally stable up to 350°C, making it suitable for high-temperature applications. Morphological studies using electron microscopy showed that the synthesized HACOF consists of spherical-shaped sub-micron particles, highlighting the success of the synthesis process. The Brunauer–Emmett–Teller (BET) surface area of HACOF was measured to be 112.4177 m²/g, with a Langmuir surface area of 126.0364 m²/g, indicating a relatively porous structure. Furthermore, the CO₂ adsorption capacity of HACOF was evaluated at 273 K, and the material demonstrated a CO₂ uptake of 0.757 mmol/g. These findings suggest that HACOF could serve as a promising candidate for applications in gas adsorption and storage, particularly in CO₂ capture, due to its thermal stability, moderate surface area, and environmentally benign synthesis approach.